A high magnetic permeability nanocrystalline cut iron core and its preparation method and application
By using specific components of grinding fluid on the cutting surface of the common mode inductor core for mechanical grinding and adding reducing iron powder, the problem of insufficient impedance characteristics of the iron core at high frequency is solved, and a significant improvement in high-frequency magnetic permeability and impedance is achieved.
Patent Information
- Application Number
- CN202211015097.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-08-23
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2042-08-23
AI Technical Summary
The prior art is difficult to achieve high impedance characteristics for common mode inductor cores at high frequencies, and the traditional C-type iron core cutting processing technology leads to a decrease in inductance/impedance.
Using a mechanical grinding method of adding grinding fluid, grinding and cooling are promoted through grinding fluid of specific components, cutting surfaces of cutting magnetic cores are repaired, and reducing iron powder is added to the grinding fluid to reduce oxidation and increase iron content.
The high-frequency permeability is restored to more than 80% of the uncut closed magnetic circuit, which significantly improves the high-frequency impedance characteristics of the iron core and ensures that the magnetic permeability of the junction does not significantly attenuate.
Smart Images

Figure BDA0003812213070000011 
Figure BDA0003812213070000071 
Figure BDA0003812213070000081
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of nanocrystalline soft magnetic materials, and in particular relates to a high magnetic permeability nanocrystalline cut iron core and a preparation method and application thereof. Background Art
[0002] In recent years, with the development of the third generation of semiconductor technology, power electronics technology has developed towards high frequency and high power. For example, the working current of modules such as on-board chargers, DC-DC converters and motor controllers of new energy vehicles is getting larger and larger. Therefore, copper bars are increasingly used in the current loops of the circuit, that is, the winding of the common-mode iron core has changed from traditional copper wire to a copper bar with high rigidity. If a closed magnetic circuit iron core is used, it can only be directly worn on the copper bar, resulting in very small effective impedance in the circuit. In order to achieve a more ideal EMC characteristic, the size of the iron core can only be greatly increased based on this, but such a design is not allowed in a limited space. The electromagnetic compatibility of the whole vehicle requires that the common-mode inductor iron core has a higher inductance / impedance. Since the inductance of the inductor is proportional to the square of the number of turns of the coil, the number of turns of the inductor must be maintained. This requires that the best form of the iron core of the common-mode inductor is a C-type structure. After the copper bar coil design and processing is completed, the C-type open iron core is directly assembled on the coil to complete the processing and installation of the inductor device. However, based on the traditional C-type core cutting process, after the open circuit is formed and the assembly is completed, the inductance / impedance of the core is reduced by an order of magnitude relative to the closed magnetic circuit. Therefore, it is very necessary to develop a C-type cut core product and processing technology with high impedance characteristics at high frequencies. The relationship between impedance and effective magnetic permeability is shown in Formula 1. From this relationship, it can be seen that the higher the magnetic permeability of the magnetic material at high frequencies, the higher its impedance value.
[0003]
[0004] Where f is the frequency, μ e is the effective magnetic permeability of the magnetic material, A e is the equivalent cross-sectional area of the magnetic material, L e is the equivalent magnetic path length of the magnetic material.
[0005] Patent CN 102500575 A discloses a method for reducing the loss of amorphous alloy C-type core sections, including the following steps: grinding the section - ultrasonic stress elimination - core drying - chemical etching of the section burrs - section cleaning - core drying. By using ultrasonic stress elimination and chemical etching of the section burrs, the air gap caused by cutting, the mechanical stress and interlayer short circuit of the section can be eliminated, and the iron loss can be reduced. However, there is no direct relationship between iron loss and magnetic permeability at high frequencies, and this method cannot improve the high-frequency impedance characteristics of magnetic materials.
[0006] Patent CN 113990650 A discloses a processing technology for a high magnetic permeability open-type transformer core, comprising the following steps: step S1: rolling a strip into an iron core; step S2: subjecting the iron core to the following heat treatment: in the first stage, heating to 400-420°C and keeping warm for 10-30 minutes; in the second stage, heating to 460-480°C and keeping warm for 90-120 minutes; in the third stage, heating to 560-570°C and keeping warm for 90-100 minutes, and reducing the temperature to 240-300°C within 20-60 minutes; step S3: after the iron core in step S2 is cooled to room temperature, it is placed in a glue solution, dried, cured, and shaped; step S4: cutting the iron core, grinding the cut surface of the cut iron core with sandpaper, and obtaining a high magnetic permeability open-type transformer core. The patent adopts a step-by-step heating treatment, and reasonable holding time is selected in each of the three stages, so that a certain degree of crystallization occurs inside the amorphous core, thereby obtaining a crystallized structure with good performance, and thus significantly improving the magnetic permeability of the high permeability open transformer core; by grinding the cut surface of the cut core, the cut surface of the core with a certain contraction is made smoother and flatter, thereby increasing the effective contact area of the core, and further improving the magnetic permeability of the high permeability open transformer core. However, during the grinding process, the grinding surface is prone to overheating, resulting in deterioration of the performance of the magnetic material, and there is a certain degree of oxidation, which leads to a decrease in the magnetic permeability of the contact surface. Summary of the invention
[0007] In view of the shortcomings and deficiencies of the above prior art, the primary purpose of the present invention is to provide a method for preparing a high magnetic permeability nanocrystalline cut iron core. The preparation method of the present invention adopts a mechanical grinding method with the addition of grinding fluid. The grinding fluid of a specific component promotes grinding and plays a cooling role at the same time, so that the cut surface of the cut magnetic core is processed more quickly to a brighter surface, and the presence of the coolant can prevent the deterioration of the magnetic material performance caused by overheating of the grinding surface, ensuring that the magnetic core has a higher magnetic permeability at high frequencies, thereby showing better impedance characteristics. And further, by adding reducing iron powder to the grinding fluid, on the one hand, the oxidation of the grinding surface can be reduced, and on the other hand, during the mechanical grinding process, part of the iron element penetrates into the grinding surface, increasing the iron content of the grinding surface, and further ensuring that the magnetic permeability of the docking surface does not significantly decay. The iron content and nanocrystalline structure of the magnetic core body have not changed, so it will not lead to an increase in the overall iron loss of the magnetic core.
[0008] Another object of the present invention is to provide a high magnetic permeability nanocrystalline cut iron core prepared by the above method.
[0009] Another object of the present invention is to provide the application of the above-mentioned high magnetic permeability nanocrystalline cut iron core in high-frequency transformers and high-power high-impedance common-mode inductor devices.
[0010] The purpose of the present invention is achieved through the following technical solutions:
[0011] A method for preparing a high magnetic permeability nanocrystalline cut iron core comprises the following preparation steps:
[0012] (1) winding or further processing the iron-based nanocrystalline alloy thin strip into a target shape to obtain an iron core;
[0013] (2) annealing the iron core of step (1) to obtain an amorphous nanocrystalline iron core having a nanocrystalline+amorphous dual-phase microstructure;
[0014] (3) subjecting the amorphous nanocrystalline iron core obtained in step (2) to a paint-immersion curing treatment;
[0015] (4) cutting the iron core solidified in step (3) into two parts to obtain a C-shaped iron core;
[0016] (5) subjecting the cut surface of the C-shaped iron core obtained in step (4) to mechanical grinding, wherein a grinding fluid containing abrasive is used for cooling during the grinding process to obtain the high magnetic permeability nanocrystalline cut iron core;
[0017] The grinding fluid containing abrasive is composed of: 20% to 40% diamond particles with a particle size of 0.2 to 15 μm, 0.2% to 1.5% NaOH, 0.5% to 1.3% rust inhibitor, 2% to 8% lubricant, 0.6% to 1.2% dispersant, and the rest is water.
[0018] Furthermore, the iron-based nanocrystalline alloy strip in step (1) is composed of Fe (100-x-y-z-α-β-γ) M x Cu y M' z Si α B β X γ , wherein M is Co and / or Ni, M' is at least one element selected from Nb, V, Mo, Ta, W, Zr, Hf, Ti, Cr, Mn, Al, Sc, Y, Zn, and Sn, and X is at least one element selected from C, Ge, P, Ga, Sb, In, and S; 0≤x≤40, 0.5≤y≤1.5, 1≤z≤5, 1≤α≤18, 5≤β≤15, 0≤γ≤3, and x+y+z+α+β+γ≤35 is satisfied.
[0019] Furthermore, the target shape in step (1) is circular, racetrack-shaped or rectangular.
[0020] Furthermore, the annealing in step (2) refers to magnetic field annealing or non-magnetic field annealing, and the magnetic field annealing is transverse magnetic field annealing or longitudinal magnetic field annealing; the transverse magnetic field refers to the direction of the magnetic lines of force of the external magnetic field being parallel to the width direction of the iron core strip, and the longitudinal magnetic field refers to the direction of the magnetic lines of force of the external magnetic field being parallel to the length direction of the iron core strip; the intensity of the magnetic field applied in the magnetic field annealing is 10 to 10000 Gs.
[0021] Further preferably, the temperature control conditions of the annealing are as shown in 1) or 2) below:
[0022] 1) Raise the temperature to 0 to 50°C below the crystallization starting temperature of the alloy strip at a rate of 1 to 15°C / min, keep at this temperature T1 for 10 to 60 minutes, then raise the temperature to above the crystallization peak temperature at a rate of 0.5 to 10°C / min, keep at this temperature T2 for 30 to 240 minutes, and then cool to below 200°C and take out of the furnace;
[0023] 2) Raise the temperature at a rate of 1 to 10°C / min to 0 to 50°C below the crystallization start temperature of the alloy strip, keep it at this temperature T1 for 10 to 60 minutes, then raise the temperature at a rate of 0.5 to 5°C / min to above the crystallization peak temperature, keep it at this temperature T2 for 30 to 240 minutes, then cool it down to below 200°C, then raise the temperature at a rate of 1 to 10°C / min to 0 to 50°C below the crystallization start temperature of the alloy strip, keep it at this temperature T3 for 10 to 60 minutes, then raise the temperature at a rate of 0.5 to 5°C / min to above the crystallization peak temperature, keep it at this temperature T4 for 20 to 240 minutes, then cool it down to below 200°C and take it out of the furnace, wherein the above T3 and T4 are 5 to 50°C higher than T1 and T2, respectively.
[0024] Furthermore, the varnish dipping and curing treatment in step (3) refers to varnish dipping and curing treatment using epoxy resin.
[0025] Furthermore, the cutting in step (4) refers to cutting using a grinding wheel, a milling machine, wire cutting, a water jet processing, or the like.
[0026] Furthermore, the mechanical grinding process in step (5) refers to mechanical grinding process using tools such as grinding wheels, sandpaper, grinding discs, and polishing cloths.
[0027] Further preferably, the rust inhibitor is at least one of a sulfonate rust inhibitor (such as sodium petroleum sulfonate, barium petroleum sulfonate, barium dinonylnaphthalene sulfonate), a fatty acid rust inhibitor (such as stearic acid, oleic acid), and an amine rust inhibitor (such as octadecylamine oleate, cyclohexylamine stearate); the lubricant is a phosphate ester lubricant or a polyether ester lubricant; and the dispersant is at least one of polyethylene glycol, polyacrylamide, sodium polyacrylate, and carboxymethyl cellulose.
[0028] Further preferably, 1% to 10% of reducing iron powder with a particle size of 0.5 to 20 μm may be added to the grinding fluid.
[0029] A high magnetic permeability nanocrystalline cut iron core is prepared by the method.
[0030] The above-mentioned high magnetic permeability nanocrystalline cut iron core is used in high-frequency transformers and high-power high-impedance common-mode inductor devices.
[0031] Compared with the prior art, the present invention has the following beneficial effects:
[0032] (1) The present invention uses a mechanical grinding method to promote grinding through a grinding fluid with specific components, while also playing a cooling role, to repair the cut surface of the nanocrystalline iron core. When two bright cut surfaces are butt-jointed together, the high-frequency magnetic permeability can be restored to more than 80% of that when the closed magnetic circuit is not cut, thereby achieving high-frequency high-impedance characteristics, which can be applied to high-current and high-power scenarios.
[0033] (2) The present invention further adds reducing iron powder to the grinding fluid, which can reduce the oxidation of the grinding surface and improve the magnetic permeability of the butt joint surface. On the other hand, during the mechanical grinding process, part of the iron element penetrates into the grinding surface, increasing the iron content of the grinding surface, further ensuring that the magnetic permeability of the butt joint surface does not significantly decay. The iron content and nanocrystalline structure of the magnetic core body do not change, so it does not lead to an increase in the overall iron loss of the magnetic core. DETAILED DESCRIPTION
[0034] The present invention is further described in detail below in conjunction with examples, but the embodiments of the present invention are not limited thereto.
[0035] Example 1
[0036] A method for preparing a high magnetic permeability nanocrystalline cut iron core according to this embodiment includes the following preparation steps:
[0037] (1) The composition is Fe bal Cu1Nb3Si 15.5 An iron-based nanocrystalline alloy ribbon of B7 (at.%) (whose crystallization starting temperature and crystallization peak temperature are 515° C. and 535° C., respectively) is wound into a ring to obtain an iron core.
[0038] (2) The iron core of step (1) is annealed, and the annealing process is to heat up to 470°C for 60 minutes, keep it warm for 30 minutes, then heat up to 550°C for 60 minutes, keep it warm for 80 minutes, and then enter the cooling stage. The cooling process is furnace cooling. During the cooling process, a transverse magnetic field with a strength of 1000Gs is applied to obtain an amorphous nanocrystalline iron core with a nanocrystalline + amorphous dual-phase microstructure.
[0039] (3) The amorphous nanocrystalline iron core obtained in step (2) is subjected to epoxy resin impregnation and curing treatment.
[0040] (4) Cutting the iron core solidified in step (3) into two parts using a grinding wheel to obtain a C-shaped iron core.
[0041] (5) The cut surface of the C-type iron core obtained in step (4) is subjected to a grinding wheel mechanical grinding process, and a grinding fluid containing abrasive is used for cooling during the grinding process. The specific formula of the grinding fluid is 30% diamond particles with a particle size of 0.2 to 10 μm, 0.5% NaOH, 0.7% sulfonate rust inhibitor, 5% polyether ester lubricant, 0.8% polyethylene glycol dispersant, and the rest is water. The grinding time is 30 minutes, 60 minutes, and 90 minutes respectively, to obtain the high magnetic permeability nanocrystalline cut iron core.
[0042] Example 2
[0043] A method for preparing a high magnetic permeability nanocrystalline cut iron core according to this embodiment includes the following preparation steps:
[0044] (1) The composition is Fe bal Cu 0.9 Nb 1.8 Si 12 An iron-based nanocrystalline alloy ribbon of B7 (at.%) (whose crystallization starting temperature and crystallization peak temperature are 470 and 485° C., respectively) is wound into a ring shape and then further fixed into a rectangle by a tool to obtain an iron core.
[0045] (2) The iron core of step (1) is annealed, and the annealing process is to heat up to 445°C for 60 minutes, keep it warm for 30 minutes, then heat up to 555°C for 60 minutes, keep it warm for 80 minutes, and then enter the cooling stage. The cooling process is furnace cooling. During the cooling process, a transverse magnetic field with a strength of 1000Gs is applied to obtain an amorphous nanocrystalline iron core with a nanocrystalline + amorphous dual-phase microstructure.
[0046] (3) The amorphous nanocrystalline iron core obtained in step (2) is subjected to epoxy resin impregnation and curing treatment.
[0047] (4) The iron core solidified in step (3) is cut into two parts by wire cutting to obtain a C-shaped iron core.
[0048] (5) The cross section of the C-type iron core obtained in step (4) is subjected to sandpaper mechanical grinding. During the grinding process, a grinding fluid containing abrasive is used for cooling. The specific formula of the grinding fluid is 20% diamond particles with a particle size of 0.2 to 10 μm, 0.3% NaOH, 0.5% stearic acid rust inhibitor, 2% phosphate lubricant, 0.6% polyacrylamide dispersant, and the rest is water. The grinding time is 90 minutes to obtain the high magnetic permeability nanocrystalline cut iron core.
[0049] Example 3
[0050] A method for preparing a high magnetic permeability nanocrystalline cut iron core according to this embodiment includes the following preparation steps:
[0051] (1) The composition is Fe bal. Cu 0.8 Nb 1.4 Si6B 10 An iron-based nanocrystalline alloy thin strip (whose crystallization starting temperature and crystallization peak temperature are 445 and 462° C., respectively) with a surface area of 1.5777 W / m2 (at.%) is wound into a ring shape and then further fixed into a rectangle by a tool to obtain an iron core.
[0052] (2) The iron core of step (1) is annealed, and the annealing process is as follows: heating to 430°C (T1) for 60 minutes, keeping the temperature for 30 minutes, then heating to 505°C (T2) for 60 minutes, keeping the temperature for 80 minutes, then cooling to 200°C and heating to 440°C (T3) for 60 minutes again, keeping the temperature at this temperature for 30 minutes; heating to 550°C (T4) again, keeping the temperature for 30 minutes, and then cooling with the furnace. During the cooling process, a transverse magnetic field with a strength of 1000Gs is applied to obtain an amorphous nanocrystalline iron core with a nanocrystalline + amorphous dual-phase microstructure.
[0053] (3) The amorphous nanocrystalline iron core obtained in step (2) is subjected to epoxy resin impregnation and curing treatment.
[0054] (4) The iron core solidified in step (3) is cut into two parts by wire cutting to obtain a C-shaped iron core.
[0055] (5) The cross section of the C-type iron core obtained in step (4) is subjected to sandpaper mechanical grinding. During the grinding process, a grinding fluid containing abrasive is used for cooling. The specific formula of the grinding fluid is 40% diamond particles with a particle size of 0.2 to 10 μm, 1% NaOH, 1.2% amine rust inhibitor, 8% polyether ester lubricant, 1.2% sodium polyacrylate dispersant, and the rest is water. The grinding time is 90 minutes to obtain the high magnetic permeability nanocrystalline cut iron core.
[0056] Example 4
[0057] Compared with Example 1, 1%, 2%, 4%, 5%, 8% and 10% of reducing iron powder with a particle size of 0.5-20 μm were added to the grinding fluid respectively, and the grinding time was 90 min. The rest was the same.
[0058] Comparative Example 1
[0059] Compared with Example 1, the section of the C-type core in this comparative example was not cooled by a grinding fluid containing abrasive during the mechanical grinding process, and the grinding time was 90 minutes, while the rest was the same.
[0060] Performance Test:
[0061] The surface roughness, magnetic permeability and iron loss of the nanocrystalline cut cores obtained in the above embodiments and comparative examples were measured at different frequencies, and the initial magnetic permeability and iron loss of the amorphous nanocrystalline cores before cutting were used for comparison. The results are shown in Table 1 below.
[0062] Table 1. Comparison of surface roughness and performance between examples and comparative examples
[0063]
[0064]
[0065] As can be seen from the results in Table 1, the present invention promotes grinding through the grinding fluid of specific components, and at the same time plays a cooling role, repairs the cut surface of the nanocrystalline iron core after cutting, and can restore the high-frequency magnetic permeability to more than 80% of the uncut closed magnetic circuit. However, the comparative example 1 that does not use the grinding fluid containing abrasive for cooling can only reach 24%. And by further adding reducing iron powder to the grinding fluid, the magnetic permeability of the cut iron core can be further significantly improved, and the iron loss can be reduced to the uncut state.
[0066] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.
Claims
1. A method for preparing a high magnetic permeability nanocrystalline cut iron core, characterized in that: The method comprises the following preparation steps: (1) Winding or further processing the iron-based nanocrystalline alloy ribbon into a target shape to obtain an iron core; (2) annealing the iron core of step (1) to obtain an amorphous nanocrystalline iron core having a nanocrystalline+amorphous dual-phase microstructure; (3) subjecting the amorphous nanocrystalline iron core obtained in step (2) to a paint-immersion curing treatment; (4) Cutting the iron core solidified in step (3) into two parts to obtain a C-shaped iron core; (5) subjecting the cut surface of the C-shaped iron core obtained in step (4) to mechanical grinding, wherein a grinding fluid containing abrasive is used for cooling during the grinding process to obtain the high magnetic permeability nanocrystalline cut iron core; The grinding fluid containing abrasive particles comprises the following weight percentages: 20% to 40% diamond particles with a particle size of 0.2 to 15 μm, 0.2% to 1.5% NaOH, 0.5% to 1.3% rust inhibitor, 2% to 8% lubricant, 0.6% to 1.2% dispersant, 1% to 10% reducing iron powder with a particle size of 0.5 to 20 μm, and the rest is water.
2. The method for preparing a high magnetic permeability nanocrystalline cut iron core according to claim 1, characterized in that: The iron-based nanocrystalline alloy strip in step (1) is composed of Fe (100-x-y-z-α-β-γ) M x Cu y M' z Si α B β X γ , wherein M is Co and / or Ni, M' is at least one element selected from Nb, V, Mo, Ta, W, Zr, Hf, Ti, Cr, Mn, Al, Sc, Y, Zn, and Sn, and X is at least one element selected from C, Ge, P, Ga, Sb, In, and S; 0≤x≤40, 0.5≤y≤1.5, 1≤z≤5, 1≤α≤18, 5≤β≤15, 0≤γ≤3, and x+y+z+α+β+γ≤35 is satisfied.
3. The method for preparing a high magnetic permeability nanocrystalline cut iron core according to claim 1, characterized in that: The target shape in step (1) is a ring, a racetrack or a rectangle.
4. The method for preparing a high magnetic permeability nanocrystalline cut iron core according to claim 1, characterized in that: The annealing in step (2) refers to magnetic field annealing or non-magnetic field annealing, and the magnetic field annealing is transverse magnetic field annealing or longitudinal magnetic field annealing; the transverse magnetic field refers to the direction of the magnetic field lines of the external magnetic field being parallel to the width direction of the iron core thin strip, and the longitudinal magnetic field refers to the direction of the magnetic field lines of the external magnetic field being parallel to the length direction of the iron core thin strip; the intensity of the magnetic field applied in the magnetic field annealing is 10~10000 Gs.
5. The method for preparing a high magnetic permeability nanocrystalline cut iron core according to claim 4, characterized in that: The temperature control conditions of the annealing are as follows 1) or 2): 1) Raise the temperature to 0~50℃ below the crystallization starting temperature of the alloy strip at a rate of 1~15℃ / min, keep at this temperature T1 for 10~60min, then raise the temperature to above the crystallization peak temperature at a rate of 0.5~10℃ / min, keep at this temperature T2 for 30~240min, and then cool to below 200℃ and take out of the furnace; 2) Raise the temperature at a rate of 1-10°C / min to 0-50°C below the crystallization start temperature of the alloy strip, keep it at this temperature T1 for 10-60min, then raise the temperature at a rate of 0.5-5°C / min to above the crystallization peak temperature, keep it at this temperature T2 for 30-240min, then cool it down to below 200°C, then raise the temperature at a rate of 1-10°C / min to 0-50°C below the crystallization start temperature of the alloy strip again, keep it at this temperature T3 for 10-60min, then raise the temperature at a rate of 0.5-5°C / min to above the crystallization peak temperature, keep it at this temperature T4 for 20-240min, then cool it down to below 200°C and take it out of the furnace. The above T3 and T4 are 5-50°C higher than T1 and T2, respectively.
6. The method for preparing a high magnetic permeability nanocrystalline cut iron core according to claim 1, characterized in that: The varnish curing treatment in step (3) refers to the varnish curing treatment using epoxy resin; the cutting in step (4) refers to the cutting using a grinding wheel, a milling machine, a wire cutting machine, or a water jet processing method; the mechanical grinding treatment in step (5) refers to the mechanical grinding treatment using a grinding wheel, sandpaper, a grinding disc, or a polishing cloth tool.
7. The method for preparing a high magnetic permeability nanocrystalline cut iron core according to claim 1, characterized in that: The rust inhibitor is at least one of sulfonate rust inhibitors, fatty acid rust inhibitors, and amine rust inhibitors; the lubricant is a phosphate ester lubricant or a polyether ester lubricant; and the dispersant is at least one of polyethylene glycol, polyacrylamide, sodium polyacrylate, and carboxymethyl cellulose.
8. A high magnetic permeability nanocrystalline cut iron core, characterized in that: It is prepared by the method according to any one of claims 1 to 7.
9. Application of the high magnetic permeability nanocrystalline cut iron core described in claim 8 in high-frequency transformers and high-power high-impedance common-mode inductor devices.
Citation Information
Patent Citations
Loss-reducing method for amorphous alloy C type iron core section
CN102500575A
High-permeability open mutual inductor magnetic core, processing technology thereof and open mutual inductor
CN113990650A
Magnet processing system and method
CN110614565A